Decentralized task allocation with coupled constraints in complex missions - Whitten, Andrew K.; Han-Lim Choi; Johnson, Luke B.; How, Jonathan P. (Proceedings of the 2011 American Control Conference, 2011)
This paper presents a decentralized algorithm that creates feasible assignments for a network of autonomous agents in the presence of coupled constraints. The coupled constraints address complex mission characteristics that include assignment relationships, where the value of a task is conditioned on whether or not another task has been assigned, and temporal relationships, where the value of a task is conditioned on when it is performed relative to other tasks. The new algorithm is developed as an extension to the Consensus-Based Bundle Algorithm (CBBA), introducing the notion of pessimistic or optimistic bidding strategies and the relative timing constraints between tasks. This extension, called Coupled-Constraint CBBA (CCBBA), is compared to the baseline in a complex mission simulation and is found to outperform the baseline, particularly for task-rich scenarios.